Indigenous and commercial isolates of arbuscular mycorrhizal fungi display differential effects in Pyrus betulaefolia roots and elicit divergent transcriptomic and metabolomic responses - Shao, Yadong; Jiang, Shangtao; Peng, Haiying; Li, Han; Li, Peigen; Jiang, Rou; Fang, Wenyi; Chen, Tingsu; Jiang, Gaofei; Yang, Tianjie; Nambeesan, Savithri U.; Xu, Yangchun; et al. (Frontiers in Plant Science, 2023)
Background Arbuscular mycorrhizal fungi (AMF) are beneficial soil fungi which can effectively help plants with acquisition of mineral nutrients and water and promote their growth and development. The effects of indigenous and commercial isolates of arbuscular mycorrhizal fungi on pear (Pyrus betulaefolia) trees, however, remains unclear. Methods Trifolium repens was used to propagate indigenous AMF to simulate spore propagation in natural soils in three ways: 1. the collected soil was mixed with fine roots (R), 2. fine roots were removed from the collected soil (S), and 3. the collected soil was sterilized with 50 kGy 60Co γ-radiation (CK). To study the effects of indigenous AMF on root growth and metabolism of pear trees, CK (sterilized soil from CK in T. repens mixed with sterilized standard soil), indigenous AMF (R, soil from R in T. repens mixed with sterilized standard soil; S, soil from S in T. repens mixed with sterilized standard soil), and two commercial AMF isolates (Rhizophagus intraradices(Ri) and Funneliformis mosseae (Fm)) inoculated in the media with pear roots. Effects on plant growth, root morphology, mineral nutrient accumulation, metabolite composition and abundance, and gene expression were analyzed. Results AMF treatment significantly increased growth performance, and altered root morphology and mineral nutrient accumulation in this study, with the S treatment displaying overall better performance. In addition, indigenous AMF and commercial AMF isolates displayed common and divergent responses on metabolite and gene expression in pear roots. Compared with CK, most types of flavones, isoflavones, and carbohydrates decreased in the AMF treatment, whereas most types of fatty acids, amino acids, glycerolipids, and glycerophospholipids increased in response to the AMF treatments. Further, the relative abundance of amino acids, flavonoids and carbohydrates displayed different trends between indigenous and commercial AMF isolates. The Fm and S treatments altered gene expression in relation to root metabolism resulting in enriched fructose and mannose metabolism (ko00051), fatty acid biosynthesis (ko00061) and flavonoid biosynthesis (ko00941). Conclusions This study demonstrates that indigenous AMF and commercial AMF isolates elicited different effects in pear plants through divergent responses from gene transcription to metabolite accumulation.